16.8k views
4 votes
What is the inverse of the function below?

What is the inverse of the function below?-example-1

2 Answers

4 votes

Answer:


f^(-1)(x)=ln(x)

Explanation:

Given function is
f\left(x\right)=e^x.

Now we need to find it's inverse so follow these steps:

Step 1: replace f(x) with y.


y=e^x

Step 2: Switch x and y.


x=e^y

Step 3: Solve for y.


x=e^y


ln(x)=ln(e^y)


ln(x)=y


y=ln(x)

Step 4: Replace y with
f^(-1)(x).


f^(-1)(x)=ln(x)

Hence final answer is
f^(-1)(x)=ln(x).

User Sunil Rawat
by
4.9k points
5 votes

ANSWER


{f}^( - 1)(x) = ln(x)

EXPLANATION

The given function is


f(x) = {e}^(x)

Let


y={e}^(x)

We interchange x and y.


x={e}^(y)

Solve for y.


y = ln(x)

This implies that,


{f}^( - 1)(x) = ln(x)

The correct answer is C

User Samuele Mattiuzzo
by
5.0k points